RETRACTED: The revised stratigraphy of the hominin-bearing site of Kromdraai (Gauteng, South Africa) and associated perspectives. Issue 114 (January 2018) - Bruxelles, Laurent; Maire, Richard; Beaudet, Amélie; Couzens, Raymond; Duranthon, Francis; Fourvel, Jean-Baptiste; Stratford, Dominic; Thackeray, Francis; Braga, José
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the co-Editors-in-Chief and the authors. The Results and Discussion of this article duplicate significant parts of book chapter "A revised stratigraphy of Kromdraai", published by L.B., R.M., R.C., F.T. and J.B. in Braga, J. and Thackeray, J.F. (Eds.), "Kromdraai. A Birthplace of Paranthropus in the Cradle of Humankind" (2016, SUN MeDIA MeTRO, pp. 31-47), https://doi.org/10.18820/9781928355076 . One of the conditions of submission of a paper to Journal of Human Evolution is that authors declare explicitly that that their work is original and has not been published previously. Reuse of any data should be appropriately cited. As such this article represents an abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.